Investing in Your Future: Developing Financial Competence for Success - Evieana R Saputri; Sani Haryati; Akmal Nurisnanto Dewatmoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study conducted at Bank Indonesia in Yogyakarta investigates the intricate relationship between financial education, access to financial resources, financial behavior, and financial competence among the bank's customers. Utilizing a quantitative research design and employing SmartPLS for data analysis, the study examines the direct and indirect effects of these variables on financial competence. Findings reveal significant direct effects of financial education and access to financial resources on financial competence, with financial behavior mediating the relationship between financial education and financial competence. However, access to financial resources does not directly influence financial behavior and competence. These results underscore the importance of comprehensive financial education programs in fostering positive financial behaviors and enhancing financial competence among individuals, thereby contributing to greater financial well-being and stability in the Yogyakarta region.